(NkOLOKOLA PO\MA DLQ SIMFONI^ESKOGO ORKESTRA HORA I SOLISTOWs (NpARTITURA(B. (NsO^(B.35s - (Ns rAHIMOWs; (NsLOWA |DGARA POs (NPEREWOD^IKs ((NmOSKWAs (NmUZYKAs, 1967)
(NkOLOKOLA PO\MA DLQ SIMFONI^ESKOGO ORKESTRA HORA I SOLISTOW s
Keywords: (NpARTITURAs